Persepsi Mahasiswa dalam Moderasi Beragama dan Relevansinya dengan Konsep Wasatha pada Mahasiswa UIN Alauddin Makassar - Tawakkal, Safira; Puyu, Darsul S.; Lewa, Irfan (Universitas Islam Negeri Alauddin Makassar, 2023)
This research discusses how the perception of students in religious moderation and its relevance to the concept of wasatha (Case Study of Comparative Schools and Law Students at UIN Alauddin Makassar). This type of research is classified as qualitative with a social approach. The data sources for this research are primary and secondary data. The results of this study indicate that: 1) Religious moderation is a bridge for people to respect each other in a life that is colored by differences. Religious moderation is not a way to create a new understanding for the most correct, the presence of religious moderation in the midst of diversity is a way that needs to be implemented at the campus world level. 2) Students of Comparative School and Law slowly accept differences in the campus environment for the sake of mutual harmony. With this, slowly the aspiration of the Chancellor of UIN Alauddin Makassar is realized, although a small portion still does not act wasatha but this is not seen in the campus environment, what is seen is the majority of students who act wasatha and understand the meaning of religious moderation. 3) The implementation of student attitudes tends to implement the values of religious moderation through behavior and attitudes by respecting each other and impartially so that there is no impartial treatment. The attitude of students is also silent with a sign of respect for people to look for sources of understanding so that they do not immediately follow and indirectly justify that the understanding is correct and must be followed. PTKIN has a duty to instill the value of moderation in its students in order to form a tolerant character.